Medication-handling challenges among visually impaired population - Ling Zhi-Han; Yow Hui-Yin; Mohd Makmor-Bakry (Archives of Global Professionals, 2017)
Objective: Visually impaired individuals are particularly at higher risk for experiencing a medication error. The aim of this study is to identify the problems encountered by the visually impaired population when handling their medication. Methods: A cross-sectional survey was conducted using an interviewer-guided questionnaire with 100 visually impaired individuals. The questionnaire comprised a series of questions in medication management. Results: All of the respondents perceived that self-administration of medication was a challenging task. A total of 89% of respondents were unable to read the prescription labels, 75% of respondents did not know the expiry date of their own medication, and 58% of respondents did not know the name of the medication. With regard to storage of medication, 72% of respondents did not practice appropriate methods to store their medication, and 80% of respondents kept the unused medication. All of the respondents disposed leftover medication through household rubbish. A total of 64% of respondents never practice medication review. Most (96%) of them did not tell health-care providers when they faced difficulties in handling their medication. Conclusion: Most of the visually impaired individuals did not receive appropriate assistance regarding medicine use and having low awareness in medication management. This can lead to increased risk of medication errors or mismanagement among visually impaired population. Hence, effective strategies, especially in pharmaceutical care services, should be structured to assist this special population in medication handling.